TAWASSUT NAHDLATUL ULAMA SEBAGAI MODEL KOGNITIF IDENTITAS KEISLAMAN MODERAT: SEBUAH ANALISIS KONSEPTUAL-TEORITIS - Hamidi, Ali (UI Cirebon (Universitas Islam Cirebon), 2025)
Religion is viewed as a divine guide for humanity, aiming to create prosperity in this world and salvation in the hereafter. However, the reality of religious practice often diverges significantly from its ideal teachings, causing religion to sometimes appear as a source of conflict rather than peace. This article analyzes the concept of Tawassut (moderation) upheld by Nahdlatul Ulama (NU) not merely as a moral encouragement but as a strong cognitive model. Through systematic literature review, the study reveals that Tawassut functions as a cognitive filter rejecting extremism, followed by a cognitive adaptation mechanism based on Tawazun (balance) that builds intellectual resilience in weighing diverse religious and social perspectives. The final stage manifests in a moderated identity through Tasamuh (tolerance) and I'tidal (justice). This cognitive model serves as an intellectual immunity system effectively neutralizing radical thinking structures while maintaining equilibrium between tradition and modernity, creed and reality, and religion and nationality. The resultant identity is inclusive, adaptive, and progressive, deeply rooted in Indonesian cultural contexts. Thus, the model offers not only theological and philosophical foundations but a practical strategy for Indonesian Muslims to live harmoniously in a pluralistic society and prevent religious conflicts. The cognitive model of Tawassut has vital implications for strengthening religious moderation in the era of globalization and information disruption.